Research and development of deck bridges - Kvocak, Vincent; Dubecky, Daniel (Springer, 2021)
This book focuses on deck bridges with encased steel beams. The chapters discuss the design process in deck bridges in the past and some current issues regarding the design and construction of this type of bridges, particularly in Slovakia. The theoretical part covers the latest achievements of international endeavours in composite bridge research. The authors provide results on research into structures with encased steel beams, based on experiments carried out solely by the Department of Structural Engineering of the Faculty of Civil Engineering at the Technical University in Kosice. The results obtained are compared with numerical simulations and analytical calculations. The book also contains some information on testing the materials of steel and concrete and their characteristics. Finally, a variety of types of composite action between steel and concrete have been examined and are discussed.